Mechanisms of enhanced force production in lengthening (eccentric) muscle contractions - Herzog, W. (Journal of Applied Physiology, 2014)
In contrast to isometric and shortening contractions, many observations made on actively lengthening muscles cannot be readily explained with the sliding filament and cross-bridge theory. Specifically, residual force enhancement, the persistent increase in force following active muscle lengthening, beyond what one would expect based on muscle length, has not been explained satisfactorily. Here, we summarize the experimental evidence on residual force enhancement, critically evaluate proposed mechanisms for the residual force enhancement, and propose a mechanism for residual force enhancement that explains all currently agreed upon experimental observations. The proposed mechanism is based on the engagement of the structural protein titin upon muscle activation and an increase in titin`s resistance to active compared with passive stretching. This change in resistance from the passive to the active state is suggested to be based on 1) calcium binding by titin upon activation, 2) binding of titin to actin upon activation, and 3) as a consequence of titin-actin binding—a shift toward stiffer titin segments that are used in active compared with passive muscle elongation. Although there is some experimental evidence for the proposed mechanism, it must be stressed that much of the details proposed here remain unclear and should provide ample research opportunities for scientists in the future. Nevertheless, the proposed mechanism for residual force enhancement explains all basic findings in this area of research.